The health gains and cost savings of dietary salt reduction interventions, with equity and age distributional aspects - Nhung Nghiem; Tony Blakely; Linda J. Cobiac; Christine L. Cleghorn; Nick Wilson (BMC, 2016)
Abstract Background A "diet high in sodium" is the second most important dietary risk factor for health loss identified in the Global Burden of Disease Study 2013. We therefore aimed to model health gains and costs (savings) of salt reduction interventions related to salt substitution and maximum levels in bread, including by ethnicity and age. We also ranked these four interventions compared to eight other modelled interventions. Methods A Markov macro-simulation model was used to estimate QALYs gained and net health system costs for four dietary sodium reduction interventions, discounted at 3 % per annum. The setting was New Zealand (NZ) (2.3 million adults, aged 35+ years) which has detailed individual-level administrative cost data. Results The health gain was greatest for an intervention where most (59 %) of the sodium in processed foods was replaced by potassium and magnesium salts. This intervention gained 294,000 QALYs over the remaining lifetime of the cohort (95 % UI: 238,000 to 359,000; 0.13 QALY per 35+ year old). Such salt substitution also produced the highest net cost-savings of NZ$ 1.5 billion (US$ 1.0 billion) (95 % UI: NZ$ 1.1 to 2.0 billion). All interventions generated relatively larger per capita QALYs for men vs women and for the indigenous Māori population vs non-Māori (e.g., 0.16 vs 0.12 QALYs per adult for the 59 % salt substitution intervention). Of relevance to workforce productivity, in the first 10 years post-intervention, 22 % of the QALY gain was among those aged <65 years (and 37 % for those aged <70). Conclusions The benefits are consistent with the international literature, with large health gains and cost savings possible from some, but not all, sodium reduction interventions. Health gain appears likely to occur among working-age adults and all interventions contributed to reducing health inequalities.